2016
DOI: 10.1016/j.euromechsol.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Computational method for excluding fibers under compression in modeling soft fibrous solids

Abstract: Abstract. Soft fibrous solids often consist of a matrix reinforced by fibers that render the material anisotropic. Recently a fiber dispersion model was proposed on the basis of a weighted strain-energy function using an angular integration approach for both planar and three-dimensional fiber dispersions (G.A. Holzapfel and R.W. Ogden: Eur. J. Mech. A/Solids, 49 (2015) 561-569). This model allows the exclusion of fibers under compression. In the present study computational aspects of the model are documented. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…This model incorporates a weighted strain-energy function and enables the Cauchy stress and elasticity tensors to be evaluated in a straightforward way. In addition, we have also discussed the integration boundary of the region that admits only extended fibers under any deformation state [23], implemented this model in the finite element analysis program FEAP [24] and verified it with several numerical examples. However, in that study, for purposes of illustration of the method, we demonstrated the new fiber dispersion model [17] by using a simple quadratic form of strain-energy function, namely the standard fiber-reinforcing model [25], for the fiber contribution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This model incorporates a weighted strain-energy function and enables the Cauchy stress and elasticity tensors to be evaluated in a straightforward way. In addition, we have also discussed the integration boundary of the region that admits only extended fibers under any deformation state [23], implemented this model in the finite element analysis program FEAP [24] and verified it with several numerical examples. However, in that study, for purposes of illustration of the method, we demonstrated the new fiber dispersion model [17] by using a simple quadratic form of strain-energy function, namely the standard fiber-reinforcing model [25], for the fiber contribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, the quadratic form of the strain-energy function is not able to capture the highly nonlinear mechanical response of some soft biological tissues such as arterial tissues, and an exponential form of the strain-energy function is more suitable for those tissues [15,26]. This can be verified by fitting the constitutive law documented in [23], which is based on the standard fiber-reinforcing model, to experimental data of of arterial tissue. It is impossible to accurately fit the highly nonlinear behavior of soft tissues, like the one in Section 3.3, by using the quadratic strain-energy function for fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed a simple procedure for excluding fibers in compression in the GST approach forms the first part of the content of the present paper. This also complements our analysis of the exclusion procedure in the AI approach contained in [10] and its implementation described in [11]. It should also be mentioned that recently an approach to exclusion of fibers in the GST model based on the use of a Heaviside function was developed in [12].…”
Section: Introductionmentioning
confidence: 55%
“…The GST model has also been used in considering inelastic effects such as damage in, e.g., [16] and [17]. We emphasize that we have already provided a detailed analysis of the exclusion of compressed fibers for the AI approach in [10], [11]; however, it seems that the AI approach has not been implemented in commercially available finite element programs.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%